Yrityskokodynamiikka ja kasvun esteet Suomessa - Annu Laurikka (The Research Institute of the Finnish Economy (ETLA), 2023)
– The report examines the dynamics of company size classes in Finland and the relationship between growth barriers and company size. It investigates how Finnish companies have moved between different company size categories from 2008 to 2020, categorizing them based on both the number of employees and revenue. The study also explores growth barriers and whether companies of different sizes face different barriers. The results suggest that companies are more likely to shrunk to a smaller size category rather than to grow into a larger one. However, most companies remain in the same size category during both the three-year and five-year observation periods. Heavy regulations and a desire to avoid debt are the most common barriers to growth experienced by companies. Statistically significant differences between size categories were observed for seven growth barriers. The smallest micro-enterprises are more likely to experience growth barriers compared to larger companies, either because they want to avoid taking on debt or because they have deficiencies in sales and marketing. Small and medium-sized enterprises (SMEs) encounter growth barriers more frequently than micro-enterprises due to higher cost levels compared to competitors. The fewest growth obstacles were encountered in the Mittelstand company size category.
Keywords: L11; L20; L21; L25; D22; 330; Company size; Company size dynamics; Growth; Growth barrier